Hubungan Ketegasan Guru Terhadap Kedisiplinan Siswa Di Kelas IV SDN 01 Tugu Harum - Puji Lestari; Wahid Hasim; Musrifah Musrifah (Jurnal Lentera Pedagogi, 2024)
This study aims to determine whether there is a relationship between teacher assertiveness and student discipline at SDN 01 Tugu Harum. In this study, the approach used is quantitative method. While the data collection techniques used are questionnaires and documentation. Based on hypothesis testing using the product moment formula above, the final value of the rtable price at a significant level of 5% is 0.2787. Thus, ∅ (which comes from changes to C) is greater than rtabel at the 5% and 1% significance levels. With this, the Null Hypothesis is rejected and the Alternative Hypothesis (Ha) is accepted, there is a relationship between Teacher Assertiveness and Student Discipline at SDN 01 Tugu Harum.